SISTEM INFORMASI PENDAFTARAN DAN PENGOLAHAN NILAI PRAKTEK KERJA LAPANGAN DI DEPARTEMEN INFORMATIKA DAN INSTRUMENTASI SEKOLAH VOKASI UNIVERSITAS GADJAH MADA - , ERNA ERVIANA, Anindita Suryarasmi, S.Kom.,M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fieldworkpracticum is an activity to apply the skill of students that derived during the college into a certain or specific job. Fieldwork practicum trains the students to know the career worlds and also to boost themselves quality. Fieldworkpracticum is a compulsory object that must be taken by student of IINâs Depertment as the requirement of graduation. Processing data of field work practicum in this department has already conducted by using computer. nevertheless, it is still less optimal due to the process of registering and processing data of score that still inefficient and ineffective. this because the processing data still runs in old manner.. Students must visit the secretariat to handlethe group registration and to request the lecturer as an advisor for their fieldwork practicum. Scoringprocess is carried out by some juries which are the student itself (teammate), fieldwork practicum advisor, examiner team, and user in which fieldwork practicum is held. Scoring process is conducted by filling the score into the form and recap by 1 person. Regardingto above circumstance, an information system of registration and processing the fieldwork practicum score has been built and able to handle the registration and score processing.This information system is built by using framework codeigniter, Mysql database and framework Jquery for the javascript. Output of this information system is the report of fieldworker in each period and score.